A nylon alloy material, a preparation method and application thereof

CN122060318BActive Publication Date: 2026-10-09SHANGHAI KINGFA SCI & TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610209527.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-13
Publication Date
2026-10-09
Estimated Expiration
2046-02-13

AI Technical Summary

Technical Problem

然而,尼龙材料受限于分子链中极性酰胺基团的影响,存在显著缺陷:其一,高吸湿性导致产品尺寸稳定性、加工性差,限制其在高尺寸精度领域的应用;其二,耐醇解能力较差,由于酰胺键的存在,尼龙材料在接触醇类介质(如甲醇、乙醇)时易发生溶胀、开裂甚至降解,这一缺陷严重制约其在新能源醇基燃料系统、生物医药容器等新兴领域的应用

Benefits of technology

本发明通过在聚酰胺中引入间规聚苯乙烯与聚酰胺组成基体树脂,同时加入丙烯腈-苯乙烯-甲基丙烯酸共聚物以及乙烯-丙烯酸酯-马来酸酐三元共聚物作为焊接促进剂或相容促进剂,协同酞菁镍产生了协效作用,能够在体系中起到促进结合的作用,同时在高温焊接过程中保持优异的界面融合能力,大幅提升了尼龙材料的焊接能力与耐醇解能力,克服了传统材料焊接后易脆化的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a nylon alloy material, which comprises the following components in parts by weight: polyamide 5-80 parts; syndiotactic polystyrene 4-41 parts; reinforcing filler 0-40 parts; acrylonitrile-styrene-methyl methacrylate copolymer 3-10 parts; ethylene-acrylate-maleic anhydride terpolymer 1-8 parts; the ethylene-acrylate-maleic anhydride terpolymer is ethylene-butyl acrylate-maleic anhydride terpolymer or ethylene-ethyl acrylate-maleic anhydride terpolymer; and the content of the polyamide and the syndiotactic polystyrene is not less than 60 wt% based on the total weight percentage of the nylon alloy material. The nylon alloy material has the advantages that the introduction of the acrylonitrile-styrene-methyl methacrylate copolymer and the ethylene-acrylate-maleic anhydride terpolymer can significantly improve the solvent resistance of the nylon alloy material, effectively improve the excellent interface fusion capacity during high-temperature welding, overcome the defect that the traditional material is easy to be embrittled after welding, and improve the welding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a nylon alloy material, its preparation method, and its application. Background Technology

[0002] Nylon (polyamide, PA), as an important engineering plastic, has been widely used in automotive manufacturing (such as engine hoods and gearbox gears), electronics and electrical (connectors, cable insulation), and daily necessities (sports equipment, functional textiles) due to its excellent mechanical strength and wear resistance. Especially under high-load conditions, Nylon 6 (PA6) and Nylon 66 (PA66) have become the preferred materials for precision gears and bearing cages due to their excellent fatigue resistance (cycle count > 10^7). However, nylon materials have significant drawbacks due to the influence of polar amide groups in their molecular chains: firstly, high hygroscopicity leads to poor dimensional stability and processability, limiting its application in high-precision fields; secondly, it has poor resistance to alcoholysis. Due to the presence of amide bonds, nylon materials are prone to swelling, cracking, and even degradation when in contact with alcoholic media (such as methanol and ethanol). This defect severely restricts its application in emerging fields such as new energy alcohol-based fuel systems and biomedical containers.

[0003] Syndiotactic polystyrene (SPS), due to its unique syndiotactic three-dimensional structure and semi-crystalline properties, exhibits excellent chemical corrosion resistance, high-temperature resistance, and dielectric properties, making it an ideal material for chemical pipeline linings, 5G high-frequency communication devices, and medical sterilization equipment. However, the industrial application of SPS is limited by two core issues: first, its intrinsic brittleness results in poor impact resistance, making it difficult to meet the requirements of dynamic load scenarios (such as automobile bumpers); second, its low melt strength makes it prone to film breakage or collapse in molding processes such as blow molding and extrusion foaming, narrowing the processing window by more than 60% compared to traditional polystyrene (PS), making it difficult to apply to parts requiring high-temperature welding.

[0004] Chinese patent application CN120272002A discloses a polyamide composite material comprising 20-80 parts polyamide resin, 5-60 parts sPS, 0.1-3 parts stannous sulfate, 0-35 parts reinforcing filler, and 0.05-6 parts compatibilizer. The compatibilizer is selected from maleic anhydride graft copolymers and fumarate-modified 2,6-dimethylphenol homopolymers. The maleic anhydride graft copolymers are maleic anhydride-grafted PP, maleic anhydride-grafted PE, and maleic anhydride-grafted POE. This polyamide composite material exhibits good mechanical properties and thermal stability. However, its resistance to alcoholysis and high-temperature welding requires further modification. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned technical defects and provide a nylon alloy material with good resistance to alcoholysis and high welding strength, as well as its preparation method and application.

[0006] This invention is achieved through the following technical solution: A nylon alloy material, by weight, comprises the following components: 5-80 parts of polyamide; 4-41 parts of syndiotactic polystyrene; 0-40 parts of reinforcing filler; 3-10 parts of acrylonitrile-styrene-methacrylic acid copolymer; 1-8 parts of ethylene-acrylate-maleic anhydride terpolymer; The ethylene-acrylate-maleic anhydride terpolymer is either an ethylene-butyl acrylate-maleic anhydride terpolymer or an ethylene-ethyl acrylate-maleic anhydride terpolymer. The total weight percentage of polyamide and syndiotactic polystyrene in the nylon alloy material shall not be less than 60 wt%.

[0007] In the nylon alloy material of the present invention, the content of polyamide can be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, etc.; the content of syndiotactic polystyrene can be 4 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 41 parts, etc.; the content of reinforcing filler can be 0 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, etc.; the content of acrylonitrile-styrene-methacrylic acid copolymer can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.; and the content of ethylene-acrylate-maleic anhydride terpolymer can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, etc.

[0008] The polyamide is selected from at least one of aliphatic polyamides and aromatic polyamides. The aliphatic polyamide can be a homopolymer obtained by polymerization of one or more amino acids or ring-opening polymerization of lactams, or a polymer of one or more dialiphatic carboxylic acids and dialiphatic amines. The aromatic polyamide can be a polymer of one or more dialiphatic carboxylic acids and diaromatic amines, or a polymer of one or more diaromatic carboxylic acids and dialiphatic amines. It can also be a copolymer of the above monomers. Optionally, the aliphatic polyamide is selected from at least one of PA6, PA11, PA12, PA46, PA56, PA66, PA610, PA612, PA1010, and PA1012; optionally, the aromatic polyamide is selected from at least one of PA6T, PA9T, PA10T, and PA6T66.

[0009] This invention does not impose any particular limitation on the characteristic parameters of the polyamide. The purpose of this invention can be achieved when the relative viscosity of the polyamide is in the range of 2.0-3.0. The test method for relative viscosity is GB / T 12006.1-2009, the test temperature is 23℃, and the solvent is 96% H2SO4.

[0010] This invention does not limit the melt index of acrylonitrile-styrene-methacrylic acid copolymer, which can be in the range of 3-20 g / 10 min, with test conditions of 230℃ / 2.16 kg.

[0011] The melt index range of the ethylene-acrylate-maleic anhydride terpolymer is 3-30 g / 10 min. The test standard for melt index is ISO 1133-2022, and the test conditions are 230℃ / 2.16 kg.

[0012] This invention does not have any special requirements for syndiotactic polystyrene; the weight-average molecular weight of syndiotactic polystyrene is 8 × 10⁻⁶. 4 -2.4×10 5 The objective of this invention can be achieved within the range of g / mol.

[0013] The test method was as follows: Referring to GB / T 36214.4-2018, a high-temperature gel permeation chromatography system (GPC-IR, Polymer Char, Spain, equipped with dual infrared and viscosity detectors) was used. 1,2,4-trichlorobenzene was used as the mobile phase, with a flow rate of 1.0 mL / min, a column temperature of 160℃, a detector temperature of 160℃, and an injector temperature of 160℃. A calibration curve was established using polystyrene standards (weight-average molecular weight range: 266-12,900,000 g / mol). The sample was dissolved in trichlorobenzene (concentration 0.125 mg / mL), and the injection volume was 200 μL. Data were processed using GPC ONE software to obtain the weight-average molecular weight (Mw).

[0014] Syndiotactic polystyrene resin can be obtained from commercial sources or by self-preparation, with the preparation method referring to CN112646066B.

[0015] Preferably, by weight, it also includes 0-2 parts of nickel phthalocyanine.

[0016] The content of nickel phthalocyanine can be 0 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, or 2.0 parts.

[0017] The reinforcing filler can be any irregular filler, fibrous filler, sheet filler, granular filler, etc., which are conventional in the art and are selected from at least one of calcium carbonate, talc, mica, wollastonite, kaolin, glass microspheres, glass fiber, and carbon fiber.

[0018] Those skilled in the art can choose whether to add 0-3 parts of processing aids according to actual needs. The processing aids may include, but are not limited to, antioxidants, lubricants, etc.

[0019] Antioxidants can be tris(2,4-di-tert-butylphenyl) phosphite; 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearate-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-Hexamethylene di(3,5-di-tert-butyl-4-hydroxy-hydrogenated cinnamamide); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine; β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl ester; triethylene glycol di[3-(3,5-dimethyl-4-hydroxyphenyl)propionate]; triethylene glycol di[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-di[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester; etc.

[0020] The lubricant may be at least one of stearate lubricants, fatty acid lubricants, and stearate ester lubricants; the stearate lubricant is selected from at least one of calcium stearate, magnesium stearate, and zinc stearate; the fatty acid lubricant is selected from at least one of fatty acids, fatty acid derivatives, and fatty acid esters; and the stearate ester lubricant is selected from pentaerythritol stearate.

[0021] The method for preparing the nylon alloy material of the present invention includes the following steps: mixing the components evenly according to the formula, and granulating the mixture by extrusion through a twin-screw extruder to obtain the nylon alloy material. The upper limit of the extrusion temperature is 0~30℃ higher than the melting point of the polyamide resin.

[0022] The present invention also provides a new energy alcohol-based fuel system component containing the above-mentioned nylon alloy material.

[0023] The present invention also provides a biomedical container containing the above-mentioned nylon alloy material.

[0024] The present invention has the following beneficial effects: This invention introduces syndiotactic polystyrene into polyamide to form the matrix resin, while adding acrylonitrile-styrene-methacrylic acid copolymer and ethylene-acrylate-maleic anhydride terpolymer as welding accelerators or compatibility accelerators. These synergistic effects with nickel phthalocyanine promote bonding within the system and maintain excellent interfacial fusion capabilities during high-temperature welding. This significantly improves the weldability and alcoholysis resistance of nylon materials, overcoming the embrittlement defects of traditional materials after welding. Detailed Implementation

[0025] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0026] PA6: M2400, Xinhui Meida, relative viscosity 2.45; PA66: EP-158, Huafeng, relative viscosity 2.7; PA612: PA612 A120, Shanghai Yinggu, relative viscosity 2.35; PA6I6T: TI1207, Shandong Guangyin, relative viscosity 2.0; PA10T: Vicnyl 600P NC013, Zhuhai Wantong, relative viscosity 2.1; MXD6: PA MXD6, Shanghai Yinggu, relative viscosity 2.5; Syndiotactic polystyrene-1: weight average molecular weight 2.02 × 10⁻⁶ 5 g / mol, self-made: At a polymerization temperature of 70℃, 3.8 L of toluene, 10.0 L of styrene, 9 L of methylaluminoxane-toluene solution (containing 15 mol of methylaluminoxane), and 2 L of pentamethylcyclopentadienyl-(3,5-di(trifluoromethyl)-4-quinolinoxy)-dimethoxytitanium / toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into the reactor, acidified ethanol was added, and the mixture was stirred thoroughly and filtered to obtain the polymer. The filter cake was vacuum dried and weighed to obtain the polymer. The polymer was refluxed in boiling acetone for 2 hours, filtered while hot to obtain the solid polymer, and then vacuum dried to obtain syndiotactic polystyrene-1.

[0027] Syndiotactic polystyrene-2: weight average molecular weight 1.81 × 10⁻⁶5 g / mol, self-made: At a polymerization temperature of 55℃, 3.8 L of toluene, 10.0 L of styrene, 9 L of methylaluminoxane toluene solution (containing 15 mol of methylaluminoxane), and 2 L of pentamethylcyclopentadienyl-(3-methyl-4-quinolinoxy)-dimethoxytitanium catalyst toluene solution (containing 10 mmol of catalyst) were added sequentially, and the timer was started. After 2 hours of polymerization, the reaction solution was carefully poured into the reactor, acidified ethanol was added, and the mixture was stirred thoroughly and filtered to obtain the polymer. The filter cake was vacuum dried and weighed to obtain the polymer. The polymer was refluxed in boiling acetone for 2 hours, filtered while hot, and a solid polymer was obtained. The solid polymer was then vacuum dried to obtain syndiotactic polystyrene-2.

[0028] Acrylonitrile-styrene-methacrylic acid copolymer: S601N, UMG ABS; Compatibility Accelerator-1: Ethylene-Butyl Acrylate-Maleic Anhydride Terpolymer, Lotader@3410, Melt Index 5g / 10min, Arkema; Compatibility Accelerator-2: Ethylene-ethyl acrylate-maleic anhydride terpolymer, Lotader@5500, melt index 20g / 10min, Arkema; Maleic anhydride-grafted PP: PC-1, Foshan Nanhai Baichen; Maleic anhydride grafted POE: N493, DuPont; Nickel phthalocyanine: Shanghai Maclean, CAS: 14055-02-8; Fiberglass: Fiberglass 301HP-3-H, Chongqing Fiberglass.

[0029] Antioxidant: IRGANOX 1098, BASF.

[0030] The preparation method of the nylon alloy material in the examples and comparative examples includes the following steps: The components are mixed evenly according to the specified ratio, and then extruded and granulated using a twin-screw extruder to obtain the nylon alloy material. The extrusion temperature is set as follows: screw length-to-diameter ratio is 32:1-48:1, and screw speed is 300-550 rpm.

[0031] PA6: Extrusion temperature 200-240℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0032] PA66: Extrusion temperature 240-280℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0033] PA612: Extrusion temperature 200-240℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0034] PA6I6T: Extrusion temperature 260-300℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0035] PA10T: Extrusion temperature 300-340℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0036] MXD6: Extrusion temperature 280-320℃, screw length-to-diameter ratio 32:1-48:1, screw speed 300-550rpm.

[0037] Test methods: (1) Welding capability: The alloy materials prepared in each embodiment and comparative example were injection molded into welding specimens of 40×10×4mm, and then subjected to vibration friction welding at a welding frequency of 240Hz and an amplitude of 1.8mm. After welding, the tensile strength of the welded specimens was tested according to ISO 527-2012 standard, which is the welding strength. The injection-molded specimens were placed in a 100℃ water bath for 2 hours, and then the welding strength was tested in the same way as above. The welding capability calculation formula is as follows: Welding capability = Welding strength after water bath ÷ Welding strength before water bath × 100%.

[0038] (2) Resistance to alcoholysis: The alloy materials prepared in each example and comparative example were injection molded into square plates of 100×100×3mm. After cooling to room temperature, the square plates were immersed in an ethylene glycol solution at 120℃ for 48 hours. After immersion, the plates were removed, wiped clean, and the surface of the square plates was observed for cracks. The evaluation level is as follows: Level 1: No obvious cracks on the sample surface, with a length of less than 0.1 mm; Level 2: The sample surface has slight cracks visible to the naked eye, with a length between 0.1-1 mm; Level 3: The sample surface has visible cracks with a length between 1-20 mm; Level 4: The sample surface has penetrating cracks with a length greater than 20 mm.

[0039] Table 1: Content (parts by weight) and test results of each component in the nylon alloy materials of Examples 1-6 Table 2: Content (parts by weight) and test results of each component in the nylon alloy materials of Examples 7-12 As can be seen from the above embodiments, the nylon alloy material of the present invention has a welding capacity of greater than 75% and an alcoholysis resistance of ≥2 levels.

[0040] Table 3: Content (parts by weight) and test results of each component in the comparative nylon alloy material As can be seen from Comparative Example 1 / 2, maleic anhydride grafted compatibilizers commonly used in this field cannot effectively improve interfacial compatibility and promote welding.

[0041] As can be seen from Comparative Examples 2-4, the purpose of this invention cannot be achieved without the presence of acrylonitrile-styrene-methacrylic acid copolymer and ethylene-acrylate-maleic anhydride terpolymer, respectively, indicating that the three play a synergistic role in the technical solution of this invention.

Claims

1. A nylon alloy material, characterized in that, By weight, it includes the following components: 5-80 parts of polyamide; 4-41 parts of syndiotactic polystyrene; 0-40 parts of reinforcing filler; 3-10 parts of acrylonitrile-styrene-methacrylic acid copolymer; 1-8 parts of ethylene-acrylate-maleic anhydride terpolymer; The ethylene-acrylate-maleic anhydride terpolymer is either an ethylene-butyl acrylate-maleic anhydride terpolymer or an ethylene-ethyl acrylate-maleic anhydride terpolymer. The total weight percentage of polyamide and syndiotactic polystyrene in the nylon alloy material shall not be less than 60 wt%.

2. The nylon alloy material according to claim 1, characterized in that, The polyamide is selected from at least one of aliphatic polyamide and aromatic polyamide.

3. The nylon alloy material according to claim 2, characterized in that, The aliphatic polyamide is selected from at least one of PA6, PA11, PA12, PA46, PA56, PA66, PA610, PA612, PA1010, and PA1012.

4. The nylon alloy material according to claim 2, characterized in that, The aromatic polyamide is selected from at least one of PA6T, PA9T, PA10T, and PA6T66.

5. The nylon alloy material according to claim 1, characterized in that, The melt index range of the ethylene-acrylate-maleic anhydride terpolymer is 3-30 g / 10 min, and the test conditions are 230℃ / 2.16 kg.

6. The nylon alloy material according to claim 1, characterized in that, The weight-average molecular weight of the syndiotactic polystyrene is 8 × 10⁻⁶. 4 -2.4×10 5 g / mol; the melt index range of the acrylonitrile-styrene-methacrylic acid copolymer is 3-20 g / 10 min, and the test conditions are 230℃ / 2.16 kg; the relative viscosity range of the polyamide is 2-3.

7. The nylon alloy material according to claim 1, characterized in that, It also includes 0-2 parts by weight of nickel phthalocyanine.

8. The nylon alloy material according to claim 1, characterized in that, The reinforcing filler is selected from at least one of calcium carbonate, talc, wollastonite, kaolin, mica, glass microspheres, glass fiber, and carbon fiber.

9. The nylon alloy material according to claim 1, characterized in that, The product also includes 0-3 parts by weight of processing aids, wherein the processing aids are selected from at least one of antioxidants and lubricants.

10. A method for preparing the nylon alloy material according to any one of claims 1-9, characterized in that, The process includes the following steps: mixing the components evenly according to the formula, and granulating them by extrusion through a twin-screw extruder to obtain nylon alloy material.

11. A component for a new energy alcohol-based fuel system, characterized in that, It contains the nylon alloy material according to any one of claims 1-9.

12. A biomedical container, characterized in that, It contains the nylon alloy material according to any one of claims 1-9.

Citation Information

Patent Citations

  • A catalytic polymerization system and polymerization method for styrene polymerization and the resulting polystyrene

    CN112646066B

  • Ultraviolet resistant nylon / acrylonitrile-styrene-acrylate resin co-mixed material

    CN101760003A

  • Polyamide composite material as well as preparation method and application thereof

    CN120272002A